The Essence of Nature and Dialectical Naturalism - Karageorgakis, Stavros; Lyrou, Konstantina (Conatus - Journal of Philosophy, 2023)
In this paper, we examine how nature is defined and perceived and address the conflict between constructivism and essentialism. By exploring modern perspectives on the concept of nature that stem from the field of social sciences, we will review the analysis of Murray Bookchin’s dialectical naturalism regarding the very essence of nature. We argue that dialectical naturalism offers a dynamic developmental concept of nature that goes beyond the context of constructivism and supports that the truth of nature can be conceived.